Poster 4 Tips Senyuman Menawan - Ab. Halim, Noorhazayti; Ahmad Khushaimi, Khairunnisa’; Sayed Kamar, Syarifah Haizan (2019)
The poster was developed in order to give information to the public on tips to get beautiful and healthy smile. This pamphlet suitable for everyone and can be used nationwide.